Odpowiedzi

2009-12-06T21:44:18+01:00
B) -2(3a-2b)-4a(2-3a+2b)=-6a +4b -8a +12a²-8ab=-14a +4b +12a²-8ab
c) (4-x)(2x+5)-4=8x+20-2x²-5x=-2x²+5x+20
d)(4-2x)(3x-3)-2x(3x+1)=12x-12-6x²+6x-6x²-2x=16x-12x²
2009-12-06T21:44:55+01:00
A] =-6a+4b-8a+12a²-8ab=12a²-14a+4b-8ab=2(6a²-7a+2b-4ab),,,,,,,,, b] =8x+20-2x²-5x-4=-2x²+3x+16,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,, c] =12x-12-6x²+6x-6x²-2x=-12x²+14x-12=-2(6x²-7x+6)
Najlepsza Odpowiedź!
2009-12-06T21:48:46+01:00
B)=(-6a)+4b-8a+12a²-8ab=(-14a)+4b+12a²-8ab
c)=8x+20-2x²-5x-4=3x+16-2x²
d)=12x-12-6x²+6x-6x²-2x=16x-12-12x²
100%dobrze :D
Specjalizuję się w wyrażeniach algebraicznych :P